THE EU/CFSP AND NATO: POSSIBILITY OF A CO-EXISTENCE AS BROTHERS-IN-ARMS? - Kaynar, Mete Kaan; AK, Gökhan (International Journal of Research -GRANTHAALAYAH, 2017)
At the outset, Europe needed to develop its defense policy and structure in line with its foreign policy while the Union was evolving in institutional enlargement process during every other 10 years of time. The reason was not behind it, but in the façade of the Union building. Otherwise the Union would not be able to enable Europe to play its full part in world affairs while the ‘security’ was gaining a key-role in the international politics and relations. Since there was a security vacuum in Europe after WW’, the US urged European states to create a sort of defence structure embedded to already-formed NATO or integrated with NATO, but including German Army in both cases. Decades had passed and in the late 1990s the European Security Defence Identity and Policy was formed up as a parallel structure to NATO systems. Eventually in the start of 2000s, the EU system turned into a Common Security and Defence Policy for member states only. This research tries to explore and analyze the effects, paradigms, prospects and coexistence possibilities of this two polar-defence-system in the Europe, that’s to say between NATO and the CFSP.